Simplify the root: -18^ sqrt(-8)^18
Follow Math Help Forum on Facebook and Google+
Hi. Originally Posted by HappyFeet Simplify the root: -18^ sqrt(-8)^18 Sorry, what exactly is the question? $\displaystyle - 18^{\sqrt{-8}^{18}} = - 18^{{(-8)^{18/2}}} = - 18^{(-8)^{9}}$ $\displaystyle = - \frac{1}{18^{8^{9}}}$ ... Regards, Rapha
Hi, I have added an attachment with the actual problem. Thanks!!!
Originally Posted by HappyFeet Hi, I have added an attachment with the actual problem. Thanks!!! $\displaystyle -\sqrt[18]{ (-8)^{18}} = - [ (-8)^{18} ]^{1/18} = -(-8)^1 = 8$.
View Tag Cloud